PERANCANGAN SISTEM INFORMASI AKADEMIK BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK CODEIGNITER (STUDI KASUS : SMK KI HAJAR DEWANTORO) - Anjas Triansyah; Nurjaya (CV. Multi Kreasi Media, 2023)
SMK Ki Hajar Dewantoro is one of the educational services located in Tangerang City. This school is located in Pinang District, Pinang Village. For data processing carried out by the SMK Ki Hajar Dewantoro, currently it is still manual by using books to process the financial bills of each student. The value input process carried out by each teacher is also still offline so this allows for errors and data loss in recording grades. The process of scheduling subjects is also still done offline, so that it becomes ineffective in data processing. By building a web-based academic information system at SMK Ki Hajar Dewantoro, it can increase in processing financial bills and minimize errors and data loss in student data processing. The design model uses Waterfall modeling and the creation of a web-based academic information system using the CodeIgniter Framework.The testing method is very important which aims to find errors or deficiencies in the software to be tested, using the Black Box testing method will be better and errors or deficiencies can be minimized. From the results of testing the system by the user through a questionnaire and calculated using the Likert scale method, the results obtained are 86% which is in the GOOD category.